SilkBase: an integrated transcriptomic and genomic database for Bombyx mori and related species. (7th June 2022) - Kawamoto, Munetaka; Kiuchi, Takashi; Katsuma, Susumu
Abstract: We introduce SilkBase as an integrated database for transcriptomic and genomic resources of the domesticated silkworm Bombyx mori and related species. SilkBase is the oldest B. mori database that was originally established as the expressed sequence tag database since 1999. Here, we upgraded the database by including the datasets of the newly assembled B. mori complete genome sequence, predicted gene models, bacterial artificial chromosome (BAC)-end and fosmid-end sequences, complementary DNA (cDNA) reads from 69 libraries, RNA-seq data from 10 libraries, PIWI-interacting RNAs (piRNAs) from 13 libraries, ChIP-seq data of 9 histone modifications and HP1 proteins and transcriptome and/or genome data of four B. mori -related species, i.e. Bombyx mandarina, Trilocha varians, Ernolatia moorei and Samia ricini . Our new integrated genome browser easily provides a snapshot of tissue- and stage-specific gene expression, alternative splicing, production of piRNAs and histone modifications at the gene locus of interest. Moreover, SilkBase is useful for performing comparative studies among five closely related lepidopteran insects. Database URL : https://silkbase.ab.a.u-tokyo.ac.jp